Hubungan antara Keharmonisan Keluarga dengan Perilaku Delinkuen pada Remaja SMP Negeri 3 Sragen - Nugroho, Dwi Sulistyo Cahyo, Dra. Partini M.Si., Psi (2016)
The purpose of this study to determine whether there is a relationship between family harmony with delinquency behavior. The hypothesis is a negative correlation between family harmony with delinquency behavior. The subject of this research were 114 students, while the population in this study were all students of SMP Negeri 3 Sragen classes VII and VIII total 443 people. The sampling technique used was cluster random sampling. Data collection tool in this study using a scale of family harmony and delinquency behavior. Data were analyzed using product moment correlation. The results of the analysis of this research that there is a significant negative relationship between family harmony with delinquency behavior. . This is indicated by the value of r xy = -0.451 with sig. = 0.000 (p <0.01). Family harmony in general subjects included in the high category. Behaviour delinquency subject is low. . Effective contribution (SE) family harmony with behavioral variable delinquency by 20.4%. This means there are 79.6% of other variables that can influence the behavior of a variable outside delinquency family harmony.